On the Implausibility of Equivalent Response (Part I) - Hu, Qian (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1992)
AbstractThis paper sets out to investigate Eugene Nida's theory of equivalent response and to decide whether it is an achievable goal for practising translators. The exposition commences with a survey of various important concepts in the linguistic field. The theory of equivalent response is compared with other approaches to the problem of obtaining translations which are both readable and faithful to the original text. The nature of language is discussed with reference to the similarities (shared characteristics) and dissimilarities (idiosyncratic features). It is asserted that language is a system of dialectical relationships which sustains translation and hinders equivalent effect at the same time.